Managing the capitalisation of agro-industrial enterprises - Davydenko, Nadiia Mykolaivna; Hordei, Oksana Dmytrivna; Skrypnyk, Halyna Oleksiivna; Novytska, Olena Valeriivna; Оксана Гордей; Надія Давиденко; Галина Скрипник; Олена Новицька (Державний податковий університет, 2024)
The agribusinesses that depend on significant financial investments for their stable existence face the need to create effective mechanisms for attracting capital reviewed in the context of the current business environment. The development and implementation of such mechanisms can significantly contribute to the growth of their market value and capitalization. This not only ensures the stability of enterprises in a volatile economic environment, but also opens up new opportunities for their development and expansion. The main purpose of the study is to systematize existing approaches to determining the market capitalization of enterprises, analyze financial indicators of agro-industrial enterprises and assess the impact of russia’s full-scale invasion on these indicators. The goal is also to identify practical aspects of market capitalization formation on the example of domestic agro-industrial enterprises whose shares are actively traded on the open market. Uncovering this goal will allow for a better understanding of the dynamics and peculiarities of capitalization in the agricultural sector in the context of economic and political factors of influence. The article analyzes the theoretical and practical aspects of capitalization of agricultural enterprises. The author also considers their role and importance in the context of market indicators that reflect the efficiency of economic activity. Particular attention is paid to the impact of russia's full-scale invasion of Ukraine on February 24, 2022 on the agricultural sector and its capitalization. The adequacy of management decisions in response to current challenges depends on an accurate and objective analysis of the situation, which is possible through in-depth analytical assessment, the article emphasizes. The authors examine in detail the dynamics of key financial indicators on the example of specific agricultural enterprises, define the main tasks and goals of assessing their financial condition. Strategies for increasing the market capitalization of agro-industrial enterprises are proposed on the basis of analytical calculations. In order to improve the current situation in the context of market capitalization of agro-industrial enterprises, the authors propose a number of strategies that will contribute to the growth of the value of shares of these companies. One of the key areas is to increase the investment attractiveness of enterprises. This can be achieved by systematically informing investors about positive changes in the activities of enterprises. This will help reduce the level of their undervaluation by the market. It is important to expand the presence of enterprises in the market, in particular through the inclusion of their shares in alternative trading platforms. In addition, it is proposed to maximize dividend payments by efficiently using net profit and developing effective strategies for the realization of attracted investments. This will help to increase the capitalization of companies. Further research in this area will focus on a detailed analysis of the market capitalization of leading agricultural companies, as well as on identifying the key factors that contribute to its increase. Such an approach will not only provide a deeper understanding of the mechanisms of agricultural sector development, but will also make a significant contribution to the overall economic development of the country.

У контексті сучасного бізнес-середовища, агропромислові підприємства, які залежать від значних фінансових інвестицій для свого стабільного існування, стикаються з необхідністю створення ефективних механізмів для приваблення капіталу. Розробка та реалізація таких механізмів може значно сприяти зростанню їх ринкової вартості та капіталізації. Це, в свою чергу, не тільки забезпечує стабільність підприємств у волатильному економічному ландшафті, але й відкриває нові можливості для їх розвитку та експансії. Основною метою даного дослідження є систематизація існуючих підходів визначення ринкової капіталізації підприємств, аналіз фінансових індикаторів агропромислових підприємств та оцінка впливу повномасштабного вторгнення росії на дані показники. Дослідження також має на меті виявлення практичних аспектів формування ринкової капіталізації на прикладі вітчизняних агропромислових підприємств, чиї акції активно обертаються на відкритому ринку. Це дозволить глибше зрозуміти динаміку та особливості капіталізації в агросекторі в умовах економічних та політичних викликів. В статті проводиться аналіз теоретичних та практичних аспектів капіталізації агропромислових підприємств, а також розглядається їхня роль і значення у контексті ринкових показників, які відображають ефективність господарської діяльності. Особлива увага приділяється впливу повномасштабного вторгнення рф в Україну 24 лютого 2022 року на агропромисловий сектор та його капіталізацію. В статті підкреслюється, що адекватність управлінських рішень у відповідь на сучасні виклики залежить від точного і об’єктивного аналізу ситуації, що можливо завдяки глибокому аналітичному оцінюванню. Автори детально досліджують динаміку ключових фінансових показників на прикладі конкретних агропромислових підприємств, визначають основні завдання та цілі оцінки їх фінансового стану. На основі аналітичних розрахунків пропонуються стратегії для збільшення ринкової капіталізації агропромислових підприємств. В якості покращення існуючої ситуації у контексті ринкової капіталізації агропромислових підприємств, автори пропонують ряд стратегій, які сприятимуть зростанню вартості акцій цих компаній. Одним із ключових напрямів є збільшення інвестиційної привабливості підприємств. Цього можна досягнути через систематичне інформування інвесторів про позитивні зміни в діяльності підприємств, що допоможе зменшити рівень їх недооціненості ринком; важливим є розширення присутності підприємств на ринку, зокрема через включення їх акцій до альтернативних торговельних платформ. Крім того, пропонується максимізувати дивідендні виплати шляхом ефективного використання чистого прибутку та розробки ефективних стратегій для реалізації залучених інвестицій, що в сукупності сприятиме збільшенню капіталізації компаній. Подальші дослідження у цій області будуть зосереджені на детальному аналізі ринкової капіталізації провідних агропромислових компаній, а також на ідентифікації ключових чинників, які сприяють її збільшенню. Такий підхід не тільки забезпечить глибше розуміння механізмів розвитку аграрного сектору, але й внесе вагомий вклад у загальний економічний розвиток країни.
Keywords: agro-industrial enterprise; agro-industrial enterprise; agricultural sector; агропромислове підприємство; агропромислове підприємство; аграрний сектор